Duration of Heart Failure Is an Important Predictor of Outcomes After Mechanical Circulatory Support. (September 2015) - Loyaga-Rendon, Renzo Y.; Acharya, Deepak; Pamboukian, Salpy V.; Tallaj, Jose A.; Cantor, Ryan; Starling, Randall C.; Naftel, David C.; Kirklin, James K.
<x xml:space="preserve">Abstract</x> Background— Heart failure (HF) progression results in worsening functional capacity and end-organ compromise. HF may occur acutely or be associated with a chronic presentation. We hypothesized that the duration of HF affects outcomes after mechanical circulatory support. Methods and Results— A total of 10 730 patients registered in Interagency Registry for Mechanically Assisted Circulatory Support (INTERMACS) who received primary implant of a mechanical circulatory support device were stratified according to the duration of HF symptoms: acute HF (AHF; ⩽1 month), sub-AHF (1–12 months), and chronic HF (Cr-HF; ≥ 12 months). AHF patients were younger with a higher proportion of women and white and with a lower prevalence of peripheral vascular disease and history of prior cardiac surgeries. Sixty percent of AHF patients were INTERMACS profile 1 at the time of implantation versus 24% and 13.2% in the sub-AHF and Cr-HF groups, respectively (P=0.0001). Patients with AHF had the highest utilization of biventricular support (14.4%). The estimated survival at 4 years was 58%, 51%, and 45% for the AHF, sub-AHF, and Cr-HF patients (P=0.006). The proportion of patients with AHF who received heart transplantation at 1 year was 29% compared with 22.6% in the patients with Cr-HF. After adjustment for known risk factors of adverse outcome, patients with AHF have a better late phase prognosis compared with patients with Cr-HF (hazard ratio, 0.34; P=0.0003). Conclusions— The duration of HF before durable mechanical circulatory support implant is an important variable influencing outcome. Patients with AHF had improved survival at 4 years and higher rates of transplantation at 1 year despite higher acuity of presentation.